Adapting roughages varying in quality and curing processes to the nutrition of beef cattle: A comparison of prairie hay and corn cobs; a special supplement vs. milo grain and cottonseed meal. - Smith, E.F.; Richardson, D.; Baker, F.H.; Cathcart, R.B.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
Forty good quality Hereford heifer calves were divided as equally as possible into four lots of 10 animals each. The heifers originated in the vicinity of Snyder. Texas. They were dehorned, vaccinated, and branded before starting the experiment. The rations used in this experiment are shown in Table 11. An attempt was made to keep the protein and total digestible nutrients on an equal basis between the prairie hay and corn cob lots. The animals receiving corn cobs as their roughage were given 50,000 International Units of vitamin A per head daily. The 3 pounds of special supplement fed daily to Lot 12 was composed of 2.25 pounds cottonseed meal, .50 pound molasses, .18 pound steamed bonemeal, .06 pound salt, and .01 pound vitamin supplement (2250 international units of vitamin A and 400 international units of vitamin D per gram). All lots were fed once daily during the morning.
Keywords: Beef; Curing process; Nutrition; Vitamin A